The culture of Nile tilapia at different salinities using a biofloc system - Souza, Rafael; Lima, Eduardo Cesar; Melo, Fabiana; Padilha, Maria Gabriela; Correia, Eudes (Revista Ciência Agronômica, 2019)
The influence of water salinity on the culture of Nile tilapia with biofloc was evaluated using indicators of water quality, zootechnical performance and animal welfare. Five treatments of different salinities were adopted (0, 4, 8, 12 and 16 g L-1) with three replications. The tilapia were cultured for 90 days and stocked in glass fiber tanks (800 L) at a density of 30 fish m-3 with a mean initial weight of 93.8 ± 0.89 g. Water temperature, chlorophyll-a, sedimentable solids and total suspended solids showed no difference between salinities (p>0.05). The levels of total ammonia nitrogen (3.94 mg L-1) and nitrite nitrogen (0.82 mg L-1) were lower at the salinity of 0 g L-1 compared to the highest salinity (16 g L-1) (p≤0.05). The final weight ranged from 256 to 280 g, with a survival rate of 97 to 100% (p>0.05), which resulted in a productivity of 7.4 to 8.4 kg m-3 (p≤0.05). Glucose was above the baseline value (≤ 60 mg.dL-1) in the 16 gL-1 treatment (76 mg dL-1), and fish growth at the salinities of 8 and 12 g L-1 showed positive allometry (3.020) compared to the other treatments. This demonstrated that it was possible to culture Nile tilapia at salinities of up to 16 g L-1, without compromising performance.